INFORMATION SYSTEM OF IDENTIFICATION OF TERMS AND ABBREVIATIONS IN TEXT DOCUMENTS - DANYLYK, VITALII; LYTVYN, VASYL; MUSHASTA, SOLOMIYA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper examines the process of building and functioning of the system for identifying terms and abbreviations in text documents. The task of developing such a system is urgent, since such an identification problem often arises in the military sphere. During the implementation of the system, it was taken into account that a single term or abbreviation may have several explanations in different regulatory documents. All available explanations are added to the term or abbreviation, which is taken into account during the operation of the system. A feature of the system is the use of natural language processing methods, since terms can be found in different cases. To implement the system, ready-made Python packages were used to cover similar tasks: Tkinter, PyMuPDF Examples of the system's functioning are given. The developed system is used in practice.In the process of completing the work, the research of problems and the search for solutions for the tasks is carried out, an information system is developed for the processing of documents with the aim of integrating definitions of potentially unknown terms and abbreviations into them, in order to enable officers to use any literature without problems, because all terms and abbreviations will be known. To generalize the documentation, all the necessary requirements for the system are defined, and in order to correctly create the architecture and allocate the functional tasks of the system under development, a system analysis is performed and a conceptual model is built. Using all the specified information, all the necessary diagrams are built using the UML notation. Diagrams depict the relationships between objects and the overall architecture of the system. The architecture of the system is built in such a way that the component systems and the system as a whole can be easily expanded. At the end of the development, testing and implementation of the project is carried out. The process of operation of the components of the system on the part of the end user and the process of deployment by the end user of the information system are described. The object of the study is the presence of slowing factors in the process of command and control carried out by commanders of tactical units, which can slow down decision-making and also affect their correctness. The subject of the study is to solve the problems of the appearance of slowing factors in the process of command and control carried out by commanders of tactical units, by means of work with military data.
Keywords: information system; natural language processing; term; abbreviation; text document